Pengaruh Kegiatan Practical Life terhadap Keterampilan Merawat Diri Anak Usia 5-6 Tahun di RA Iqra' Sabila Kota Jambi - Siska Sulistiani; Tumewa Pangaribun; Asih Nur Ismiatun (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine the effect of practical life activities on self-care skills of children aged 5-6 years at RA Iqra' Sabila Jambi City. This research was conducted using a quantitative approach with a quasi experimental research design. The population amounted to 48 children at RA Iqra' Sabila Jambi City. The sample amounted to 24 children purposive sampling technique. The instrument used was an observation sheet. Data analysis techniques use normality test, homogeneity test and hypothesis testing using independent sample t test with the help of SPSS. The average research results of the experimental class on the prettest 8.41 on the posttest increased 18.00. The average control class on the prettest 8.33 and on the posttest 10.92. The test results show the sig value. (2-tailed) 0.001 <0.05, then Ho is rejected and Ha is accepted. The tcount value of 4.005 is higher than the t table 1.1714 so that ho is rejected and ha is accepted, so it can be concluded that there is an effect of practical life activities on self-care skills for children aged 5-6 years at RA Iqra' Sabila Jambi City.